تعلم مهارة القراءة عبر موقع الانترنت للناطقين بغير العربية - نورعاشقين بنت عثمان
This study attempts to ascertain the contribution of the Internet and the multi-media materials in teaching and learning processes especially with regard to reading skills. It is a descriptive and analytical study which depends primarily on fieldwork to obtain the results. The samples comprise students of Universiti Darul Iman Malaysia who passed the Arabic language subject in the Malaysian Certificate of Education (SPM). The researcher has designed a special website (www.belajararab.com) to obtain the field data pertaining to the learning of reading skills through internet. In this website, the contents of the syllabus are uploaded together with some additional multimedia materials (audio, pictures and sounds). Some links are also provided in view of two theories: The Cognitive Theory on learning through multi-media (Mayer, 2002) and Constructivist Theory (Jonassen, 2000). After the completion of the fieldwork, a number of findings could be reported. One important finding is that learning through the internet website which provides multimedia materials and good links contributed toward better grasp of the syllabus among the students, especially the average ones, as there is a statistically significant difference between the high performers and the average performers in terms of comprehension and understanding. There is also a significant correlation between the linguistic competency of the students and the level of achievement. These findings confirm the results of some previous studies which show that average students are able to achieve excellent performance from learning through the internet and multimedia.